CONSIDERATIONS ON BEEF PRODUCTION, CONSUMPTION AND TRADE BALANCE IN ROMANIA (2007-2015) - Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the dynamics of bovine meat live stock, production, live weight at slaughter, carcass weight, beef and veal consumption, beef supply, export and import and trade balance of Romania in the period 2007-2015 using the empirical data provided by the National Institute of Statistics. The analysis led to important conclusions. Beef comes on the 3rd position after poultry meat an pork in Romania. Beef production declined and so that imports were needed to cover the gap between production and consumption. The decline of the bovine live stock is the main cause as farmers are facing with high farm inputs prices and receive a low farm gate price per kg live weight. In the structure of the slaughtered bovines cows represent over 50 %, fattened steers 25 % and other categories ( bulls, heifers, calves etc). The average live weight and quality at slaughter is lower compared to other EU countries. The slaughter rate is less than 50 %. Only 26 % of bovines are slaughtered in industrial specialized units, where the fattened steers of high quality and over 400-430 kg live weight per head are usually slaughtered. Beef consumption is low as pork and poultry meat are preferred by consumers and beef price is too high. Romania is a net exporter of bovine meat, but the highest share in the export structure belongs to bovine live weight (84.4%). In 2020, it is expected as bovine live weight at slaughter to reach 235 thousand tons for an annual growth of 7 thousand tons. To develop meat production it is needed to create farmers associations, to raise meat breeds and apply modern fattening technologies.